Developing a Theoretical Framework for Implementation of Risk Management Process in Iranian Construction Projects - Rasooli, Payam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Comprehensive research studies have been conducted in recent years, specifically about risk management in construction projects, resulting in establishing methods of risk management with improved performance and efficiencies, benefitting for the companies and industries. However, there are still lacks in this area. Lack of enough knowledge about the structured methods of risk management is still significant, preventing the methods from being widely employed. This master thesis is a research carried out on steel-framed structure buildings in Iranian construction projects, investigating the risk management methods in five different stages of the construction, which are earthwork, reinforcement, formwork, concrete work and steel structure. Perception and employment methods of risk management have been studied in the mentioned stages, which has been done through questionnaire surveys and checklists. To do so, 35 members of top Iranian construction companies were chosen and asked to participate in the survey, where 20 of them participated and answered the questionnaires and checklists and as a result, response rate was found to be 57.1%. To develop the risk identification efficiently, Risk Breakdown Structure was also employed. These methods were selected to be done among a certain number of construction companies. To assess the likelihood of risks occurrence, and their impact on projects objectives, qualitative analysis method was implemented through probability and impact matrix. The assessments were done separately on each objective, i.e. time, cost, quality, and health and safety, resulting in determination of 30 main risks. An explicit result of the survey was the unfamiliarity of the Iranian construction companies with the formal methods of risk management. It was found that most of the companies are still dependent on the previous experiences, checklist and brainstorming methods and consultations to identify the potential risks and face with them. This unfamiliarity which could be due to lack of education, has been focused in this research and in fact, in this study, it has been tried to develop responding techniques to the potential risks, which have been identified as high risks, in order to have more efficient risk management. Keywords: Iranian construction industry, steel structure buildings, qualitative method, risk management, risk management process

ÖZ : Son yıllarda, özellikle inşaat projelerindeki risk yönetimi alanında, endüstri ve şirketler için yarar sağlayabilecek ve daha etkili ve gelişmiş bir performansla sonuçlanacak risk yönetimi metotları geliştiren kapsamlı araştırmalar yapılmıştır. Ancak, bu alanda yapılan araştırmalar yetersiz bulunmaktadır. Risk yönetiminin metotları ile ilgili bilgi eksikliği, bu metotların geniş alanlarda uygulanmasını engelleyerek önemli bir sorun haline gelmiştir. Bu yüksek lisans tezindeki araştırma, İran inşaat projelerinin çelik yapılı binaları üzerine gerçekleştirilmiştir. Araştırma, inşaatın toprak çalışması, demir donatı, kalıp, beton işi ve çelik yapı gibi beş farklı sürecindeki risk yönetimi metotlarını araştırmaktadır. Adı geçen süreçlerdeki risk yönetimi metotlarının algısı ve kullanımı, anket ve kontrol listesi kullanılarak araştırılmıştır. Risk tanımlamayı etkili bir şekilde geliştirmek için Risk Çözümleme Yapısı da kullanılmıştır. Bu metotlar, belirlenen bir sayıdaki şirketlerde kullanılmak için seçilmiştir. Risk oluşum olasılıklarını ve proje amaçları üzerindeki etkilerini değerlendirebilmek adına nitel metotlar, olasılık ve etki tablosu ile uygulanmıştır. Süre, maliyet, kalite, sağlık ve güvenlik gibi belirlenen 30 temel için ayrı değerlendirmeler yapılmıştır. Risk yönetiminin resmi metotlarının, İran inşaat şirketleri tarafından bilinmemesi anketlerin belirgin sonuçlarından birini oluşturmaktadır. Olası risklerin tanımlanması ve alınacak olan önlemlerin belirlenmesi için şirketlerin hala eski deneyimleri, kontrol listeleri, beyin fırtınası yöntemleri ve danışmanlıklara bağımlı oldukları sonucuna varılmıştır. Metotların bilinmemesinin, eğitim eksikliğinden kaynaklandığı düşünülmüştür ve bu konu araştırmanın odak noktalarından biri haline gelmiştir. Ayrıca bu çalışmada, yüksek risk olarak tanımlanan olası riskler karşısında, daha etkili bir risk yönetimi geliştirmek adına, yanıtlamam tekniklerinin geliştirilmesi amaçlanmıştır. Anahtar Kelimeler: İran inşaat endüstrisi, çelik yapı binaları, nitel metot, risk yönetimi, risk yönetimi süreci
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2014. Supervisor: Assist. Prof. Dr. Alireza Rezaei.
Keywords: Civil Engineering; Construction Industry - Iran; Iranian construction industry; steel structure buildings; qualitative method; risk management; risk management process